2022
DOI: 10.47772/ijriss.2022.6701
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sorghum Legume Intercroping System in Improving Soil Productivity on Small Holder Farmers in Western Kenya

Abstract: Declining crops yield in the smallholder farmers cropping systems of sub-Saharan African (SSA) present the need to develop more sustainable production systems. Depletion of essential plant nutrients from the soils have been cited as the main contributing factors due to continues cultivation of cereal crops without application of organic/ inorganic fertilizers. Field experiments to evaluate effect of phosphorus (P) fertilizers, organic and integration of legumes in sorghum cropping systems on soil, available ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Essentially, the findings suggest that potato farmers are utilising the available resources more efficiently. These results were in line with Sultana et al [2] and Barasa et al [39], who also emphasized the crucial role of farm size in increasing the technical inefficiency of smallholder farmers. However, it is worth noting that these results contradict the findings of Mengui et al [32] who observed that farm sizes had a negative influence on technical efficiency.…”
Section: Technical Inefficiencies Of Potato Enterprisesupporting
confidence: 89%
“…Essentially, the findings suggest that potato farmers are utilising the available resources more efficiently. These results were in line with Sultana et al [2] and Barasa et al [39], who also emphasized the crucial role of farm size in increasing the technical inefficiency of smallholder farmers. However, it is worth noting that these results contradict the findings of Mengui et al [32] who observed that farm sizes had a negative influence on technical efficiency.…”
Section: Technical Inefficiencies Of Potato Enterprisesupporting
confidence: 89%
“…Galabada et al (2014) in Sri Lanka found that there were opportunities in improving resource use efficiency in potato farming. Barasa et al (2019) in Kenya reported that the mean technical efficiency of potato farmers was estimated at 65%. They found that technical efficiency was positively influenced by the age of the farmer, education years, farming experience, frequency of extension services, and land size, whereas negatively influenced by household size.…”
Section: Introductionmentioning
confidence: 99%